Fabrication and spectroscopic properties of tellurite glass containing rice husk - Siti Nur Hajrah Piara (2020)
One of the main components that play an important role in the building design is glass windows. The glass must possess good heat reflection properties to reduce heat enters the building. The aim of this study is to fabricate glass with incorporation of rice husk (RH) as additive materials. This method can be a fruitful solution to overcome the emerging issue by reflecting heat and lowering the temperature in the interior buildings by using eco-friendly materials to reduce waste. Tellurite glasses are used as host glass with the composition of 69.5Te0; - 20ZnO - 10Na0 0.5Er0% - 0.2 (X) RH, where X is the RH in the form of fibre and ash with distinctive sizes of 38 μm, 63 μm, 125 μm, 250 μm and 500 μm. Two series of glass have been prepared in which the first series of glass containing rice husk fibre (RHF) and the second series of glass containing rice husk ash (RHA). All glass samples are transparent in nature and exhibit yellowish-orange in colour. SEM image shows the porosity of glass surface. EDX spectra revealed the appearance of C, 0, Na, Zn, Te, Mg, Ca, Mn, Fe, Al, Si, P, and Er elements in glass samples. XRD spectra validate the amorphous nature of glass samples with appearance of broad hump in the range of 25° - 35° and the absence of sharp peak. Meanwhile, the FTIR spectra in the range of 400 to 4000 cm+ signify the contribution of Te-O bonds, anti-asymmetric stretching of O-Si-O, stretching vibration of C=C and the presence of CO; in glass. The variation in the direct optical energy bandgap (3.0977 - 3.2935 eV), indirect optical energy bandgap (2.7189 - 3.0688 eV) and Urbach energy (0.1313 - 0.2034 eV) in the glass samples is due to the contribution from RHF and RHA. The UV-VisNIR spectra revealed the variations in the transmittance, reflectance and absorbance spectra in the ultraviolet, visible and near infrared region due to the incorporation of RHF and RHA of distinctive sizes. Glass sample containing 63 m RHF shows the optimum properties due to highest reflectivity of VIS and NIR radiation in the range of 79.32% and 79.73%.